2015
DOI: 10.1016/j.ijmedinf.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Computer versus physician identification of gastrointestinal alarm features

Abstract: Objective It is important for clinicians to inquire about “alarm features” as it may identify those at risk for organic disease and who require additional diagnostic workup. We developed a computer algorithm called Automated Evaluation of Gastrointestinal Symptoms (AEGIS) that systematically collects patient gastrointestinal (GI) symptoms and alarm features, and then “translates” the information into a history of present illness (HPI). Our study's objective was to compare the number of alarms documented by phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Another strength is our use of a novel online digital health tool that uses validated NIH PROMIS item banks and GERD-specific questions to systematically gather comprehensive information from respondents. 16,19,49 This digital platform also allowed us to efficiently recruit a large, highly diverse, representative population in a very short period of time.…”
Section: Discussionmentioning
confidence: 99%
“…Another strength is our use of a novel online digital health tool that uses validated NIH PROMIS item banks and GERD-specific questions to systematically gather comprehensive information from respondents. 16,19,49 This digital platform also allowed us to efficiently recruit a large, highly diverse, representative population in a very short period of time.…”
Section: Discussionmentioning
confidence: 99%
“…Another strength is use of a novel online digital health tool that employed validated NIH PROMIS questionnaires and computerized adaptive testing to systematically gather comprehensive GI symptom information from respondents. (21, 27, 28) This allowed us to efficiently gather data from a very large cross-section of the general U.S. population; we recruited over 71,000 respondents in the span of three weeks. Moreover, leveraging an online platform is less resource intensive compared to other population-based surveys that require significant investments in infrastructure and personnel to conduct household and telephone interviews.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were guided through a set of questions measuring the timing, severity, frequency, location, quality, and character of each reported GI PROMIS symptom, along with relevant comorbidities, family history, and alarm features. (19, 20) Once the questions were completed, the information was transformed into a full narrative GI HPI that accompanied the PROMIS heat map (Figure 1). In a previous head-to-head trial comparing GI PROMIS-directed computerized HPIs vs. physician HPIs, we found that the computerized HPIs were rated by blinded reviewers to be of higher quality and more thorough, complete, succinct, and relevant.…”
Section: Methodsmentioning
confidence: 99%